Toward a Moderate Autoethnography - Sarah Stahlke Wall (International Journal of Qualitative Methods, 2016)
Autoethnography is an avant-garde method of qualitative inquiry that has captured the attention of an ever-increasing number of scholars from a variety of disciplines. Personal experience methods can offer a new and unique vantage point from which to make a contribution to social science yet, autoethnography has been criticized for being self-indulgent, narcissistic, introspective, and individualized. Methodological discussions about this method are polarized. As an autoethnographer and qualitative methodologist with an interest in personal experience methods, I have had the opportunity to review several autoethnographic manuscripts over the years. As my reviews accumulated, I began to see themes in my responses and it became apparent that I was advocating for an approach to autoethnography that lies in contrast to the frequently offered methodological polemics from philosophically divergent scholars. In this article, I draw from the reviews I have done to address topics such as applications and purposes for autoethnography, the degree of theory and analysis used within the method, data sources and dissemination of findings, and ethical issues. I then connect the concerns I see in the reviewed manuscripts to examples in the autoethnographic literature. Ultimately, I propose a moderate and balanced treatment of autoethnography that allows for innovation, imagination, and the representation of a range of voices in qualitative inquiry while also sustaining confidence in the quality, rigor, and usefulness of academic research.